Analysis of the Effectiveness of Barista Interpersonal Communication (Case Study at Siliwangi Coffee Shop, Bandung) - Ahmadi, Farhan; Destiwati, Rita (Universitas Syiah Kuala, 2019)
Objective This study aims to analyze the effectiveness of interpersonal communication in selected coffee shops in Siliwangi, Bandung, Indonesia. This study is drawn on the phenomenon of the importance of baristas having effective interpersonal communication skills in line with the recent growth of coffee shops.Design/methodology To explain the social reality that occurs naturally in Kedai Kopi Siliwangi this study utilizes descriptive qualitative methods to describe the role of interpersonal communication that occurs between baristas and customers in increasing customer loyalty.Results In general interpersonal communication has been carried out effectively and is able to change the attitudes and behavior of customers. Barista of Kedai Kopi Siliwangi has mostly fulfilled the five aspects of the effectiveness of interpersonal communication, except that the aspect of empathy is still not optimal.Limitation/Suggestion This study may be limited in covering more comprehensive aspects of communication strategies. Future studies are hence suggested to embark research on effective management and communication strategies, both verbal and digital visual in the coffee shop. These themes can complement the viewpoints and expectations of the community towards the growing coffee shop.